Aivilik Inuit woman, Shoofly [Nivisanaaq], Hudson Bay, Canada - Comer, George (Creator) (Ownership Statement: Mystic Seaport, 1901)
An Aivilik Inuit woman identified as Shoofly [Nivisanaaq] stands outdoors at Cape Fullerton, Hudson Bay, Canada, May 17, 1901. She wears a parka, or Amautiq, decorated with trade beads. Lifestyle Title supplied by cataloger. Information from original envelope identifies this as Photo #27, # 56. Beads were obtained from the whalers as trade goods. The Aivilik or Aivillingmiut are a group of Iglulik Inuit. These Inuit of the west coast region of Hudson Bay were closely associated with Captain George Comer and the American whalers for many years. Taken by Captain George Comer (1858-1937), a sealer and whaling captain from East Haddam. He went to sea while still in his teens and was later master of vessels from both New London and New Bedford. Comer participated in voyages involved in polar expeditions and was noted for his studies of Arctic peoples and their environment.